Attention citizens in the public sector compared with customer service in a private financial institution (2013)
Citizen services is one of the biggest challenges of public entities is why this article makes a comparison between them and a financial institution in the private sector to identify opportunities for improvement. Concepts, standards and technology to identify advantages and disadvantages of public entities is developed and finally concluded between the relevant points of comparison, the current regulations and the scope in the public sector.